2013
DOI: 10.1089/ars.2012.4535
|View full text |Cite
|
Sign up to set email alerts
|

Carbamyl Adducts on Low-Density Lipoprotein Induce IgG Response inLDLR−/−Mice and Bind Plasma Autoantibodies in Humans Under Enhanced Carbamylation

Abstract: These data give insight into mechanisms of in vivo humoral recognition of post-translationally modified structures. Humoral IgG immune response to carbamylated proteins is suggested to play a role in conditions leading to enhanced carbamylation, such as uremia and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…Protein carbamylation creates potential neoepitopes that induce multiple autoantibody responses. 93-96 Rheumatoid arthritis (RA) is a disease associated with multiple types of autoantibodies, and when investigators examined if anti-carbamylated protein antibody levels are elevated in RA patients, they found that anti-homocitrulline antibodies are present and at a higher level in individuals with RA and arthralgias compared to healthy controls. They also showed positive associations with joint damage and could predict disease development in “pre-RA” patients independent of established biomarkers.…”
Section: Pathogenesismentioning
confidence: 99%
“…Protein carbamylation creates potential neoepitopes that induce multiple autoantibody responses. 93-96 Rheumatoid arthritis (RA) is a disease associated with multiple types of autoantibodies, and when investigators examined if anti-carbamylated protein antibody levels are elevated in RA patients, they found that anti-homocitrulline antibodies are present and at a higher level in individuals with RA and arthralgias compared to healthy controls. They also showed positive associations with joint damage and could predict disease development in “pre-RA” patients independent of established biomarkers.…”
Section: Pathogenesismentioning
confidence: 99%
“…Carbamylated LDL are immunogenic inducing IgG autoantibodies in LDL-deficient receptor mice [147]. These antibodies are cross-reactive with oxidative-specific epitopes, especially with MDA-LDL [148] suggesting that carbamylated LDL are partially oxidized.…”
Section: Ldl Modificationsmentioning
confidence: 99%
“…11 MDA and phosphocholine (PC) epitopes in plasma apoB-containing particles were determined as described previously. 35 Rgp44 and Rgp15-27 are consecutive sequences at the hemagglutinin/adhesin domain of gingipain. 36 PC-BSA (PC-conjugated BSA) was purchased from Biosearch Technologies (#PC-1011; Novato, CA, USA).…”
Section: Chemiluminescence Immunoassaysmentioning
confidence: 99%